2016
DOI: 10.1007/s40271-016-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Functional Limitations in the First Year Following a Myocardial Infarction: A Qualitative Study

Abstract: Patients reported a wide variety of symptoms and functional limitations after an MI. Fatigue was the most commonly reported symptom and included several specific dimensions related to tiredness. Consideration of these concepts associated with the patient's experience following an MI may yield novel endpoints for use in clinical trials and better therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In addition, it may be useful to develop and prospectively evaluate risk-stratified clinical management pathways after TAVI based on these baseline predictors in order to increase patient safety both in the short-term and in the midterm. Similar to PROM findings reported in patients after myocardial infarction [33], the patients' experience after TAVI (especially the one depicted by KCCQ and EQ5D5L) may yield novel endpoints for use in clinical trials.…”
Section: Implications For Future Studiessupporting
confidence: 55%
“…In addition, it may be useful to develop and prospectively evaluate risk-stratified clinical management pathways after TAVI based on these baseline predictors in order to increase patient safety both in the short-term and in the midterm. Similar to PROM findings reported in patients after myocardial infarction [33], the patients' experience after TAVI (especially the one depicted by KCCQ and EQ5D5L) may yield novel endpoints for use in clinical trials.…”
Section: Implications For Future Studiessupporting
confidence: 55%
“…In the study, it was observed that EDS is associated with a higher risk of re-infarction than in patients without EDS, and it was established as an independent risk factor for adverse cardiac outcomes in post-MI patients [ 24 ]. Sleep disturbances along with fatigue were one of the most common symptoms affecting patients post-MI [ 25 ]. Sleep apnea and MD are independently associated with adverse cardiac outcomes post-MI [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…(p3) may be triggered by memories of past cardiac events, thinking about having another cardiac event, or the consequences of another cardiac event. 14,25,26 On the other hand, individuals may experience improvement in HFA with certain cardiac interventions. In a prospective cohort study of 26 participants with heart failure, Sager et al 6 found that individuals experienced reduced HFA, particularly in the domain of fear, after implantation of a wireless hemodynamic monitor.…”
Section: Qualitative Descriptivementioning
confidence: 99%
“…9 This pattern leads to more episodes of HFA. 9 In a qualitative study by Gwaltney et al, 25 chest pain was a common symptom experienced by participants after MI, occurring with exertion, at rest, and with feelings of anxiety.…”
Section: Consequencesmentioning
confidence: 99%